Re-examining the New "Greeneration" behaviors: How Does the Sequential Mediation role of Green Word of Mouth and Green Trust affect Green Purchase Intention among Generation Z? - Rahmawati; Nur Hidayati; Wathanan Srinin; Ahmad Taufiqurijal (Jurnal Manajemen Teori dan Terapan)
Objective: This study explores whether and how the Z generation's perspective toward greenwashing perceptions influences their green purchasing intentions through the underlying green trust and green word of mouth.